UPAYA PERLINDUNGAN HUKUM TERHADAP PEKERJA PERKEBUNAN KOPI DI KABUPATEN JEMBER - Fanggi, Rosalind Angel (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2016)
The dominance land use of the region Jember City is for agricultural activities that area of 5099.283 hectares or 51.47% of the total area of the city. The economic life of the city is more supported by agricultural activities. This condition also occurs in Jember city where good agriculture crop farming and horticulture. The attention to the protection of workers' safety coffee plantations in Jember become essential given that are the basis for improving the quality of the coffee commodity itself. The rise of workplace accidents and lack of attention to workers in the spotlight of its own in the world of the coffee plantation. If workers can work well and healthy then it is not only companies benefiting but the state in its capacity to build the people's welfare have been realized.